Influence of Video Speeds on Visual Behavior and Decision-Making of Amateur Assistant Referees Judging Offside Events - Luis Del Campo, Vicente; Morenas Martín, Jesús (Frontiers in Psychology, 2020)
The aim of the study was to assess the effects of manipulating video speeds on visual behaviour and decision accuracy of 10 amateur football assistant referees when perceived video sequences of 24 possible offside actions on a large screen. An eye tracker was used to analyze participants' visual behaviours. Signal detection analysis provided further detail of participants´ decision-level accuracy. Participants were required to decide when they perceived a player to be offside during observed sequences with different video speed manipulations (Normal speed, 2 speed, 3 speed). Results revealed that the manipulation of video speed did not attune emergent gaze patterns differently because participants displayed similar visual behaviours, regardless of speed. However, the normal speed resulted in a higher percentage of correct decisions than the 3 speed. The participants tended towards non-flagging decision bias errors when judging offsides with the 3 speed because they made more misses, than false alarms.